Indonesian EFL Students’ Voices on Online Learning During COVID-19 Through Appraisal Analysis - Almendo Pasaribu, Truly; Dewi, Novita (LEARN Journal: Language Education and Acquisition Research Network, 2021)
During the COVID-19 pandemic, the closure of universities and colleges has caused teachers and students to alter technology enhanced courses and blended courses to a fully online learning following the call for practicing social distancing. Since adjustment to online learning requires much effort from both the teachers and the students, getting in-depth insights from the students’ voices during this pandemic through scrutinizing their reflections is important. This study aimed at investigating the attitudinal resources in reflections on online courses during COVID-19 by EFL students in Indonesia. This qualitative research employed a content analysis method to scrutinize 261 expressions. The data gathered from the students’ reflections were analyzed through the Appraisal framework (Martin & White, 2005), which captured the linguistic evidence of various attitudinal resources in expressing feelings and opinions found in their reflections. The linguistic resources reflect that the students experience this exceptional situation personally which also leads to the development of their autonomy and engagement. This study also discusses some implications to consider in maximizing the potential of online learning.